2021
DOI: 10.3390/cancers13123016
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Epigenetic Biomarkers in Liquid Biopsy for High Incidence Malignancies

Abstract: Early alterations in cancer include the deregulation of epigenetic events such as changes in DNA methylation and abnormal levels of non-coding (nc)RNAs. Although these changes can be identified in tumors, alternative sources of samples may offer advantages over tissue biopsies. Because tumors shed DNA, RNA, and proteins, biological fluids containing these molecules can accurately reflect alterations found in cancer cells, not only coming from the primary tumor, but also from metastasis and from the tumor micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 194 publications
(233 reference statements)
0
39
0
Order By: Relevance
“…These genes appear to be involved in various signaling pathways, usually disrupted in CM, such as the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and MAPK pathways, cell cycle, DNA repair, retinoblastoma (RB) and Wnt signaling [ 86 ]. Furthermore, it was also observed that three TSGs are frequently inactivated by methylation: RASSF1A (55%), RAR-β2 (70%), and MGMT (34%) can also be identified in the circulating tumor DNA of CM patients, which makes them useful diagnostic and prognostic biomarkers in the clinical setting [ 88 , 89 ]. In several cancers, but also in a significant proportion of melanomas, a gradual increase in DNA hypermethylation was observed along with tumor aggressiveness; this phenomenon, called CpG methylator phenotype (CIMP), was reported for the first time in colorectal cancers, a finding that highlighted a tight correlation between altered DNA methylation patterns and the clinical outcome of the affected patients.…”
Section: Epigenetic Alterations Driving CM Initiation and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes appear to be involved in various signaling pathways, usually disrupted in CM, such as the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and MAPK pathways, cell cycle, DNA repair, retinoblastoma (RB) and Wnt signaling [ 86 ]. Furthermore, it was also observed that three TSGs are frequently inactivated by methylation: RASSF1A (55%), RAR-β2 (70%), and MGMT (34%) can also be identified in the circulating tumor DNA of CM patients, which makes them useful diagnostic and prognostic biomarkers in the clinical setting [ 88 , 89 ]. In several cancers, but also in a significant proportion of melanomas, a gradual increase in DNA hypermethylation was observed along with tumor aggressiveness; this phenomenon, called CpG methylator phenotype (CIMP), was reported for the first time in colorectal cancers, a finding that highlighted a tight correlation between altered DNA methylation patterns and the clinical outcome of the affected patients.…”
Section: Epigenetic Alterations Driving CM Initiation and Progressionmentioning
confidence: 99%
“…Given the critical roles of epigenetic alterations in CM development and its drug resistance, targeting or co-targeting these epigenetic events appears to be a promising strategy for improving the clinical condition of CM patients [ 109 ]. Although epigenetic biomarkers have not yet found their place in clinical practice, an impressive number of epigenetic drugs are constantly being developed and tested for their cytotoxicity and efficacy in clinical trials in various human cancers, including CM [ 89 , 202 ]. These epigenetic drugs include both general epigenetic inhibitors such as HDACi or DNMTi, but also more specific inhibitors targeting enhancer of zeste homolog 2 (EZH2i), bromodomain and extra-terminal domain proteins (BETi), or JMJD3 and JARID1B demethylases [ 203 ].…”
Section: Epigenetics-based Therapies For CMmentioning
confidence: 99%
“…Liquid biopsy evaluation of epigenetic biomarkers is an emerging field in oncology that might have a putative impact in improving diagnostic and screening procedures [ 196 ]. Several benefits may address the use of DNA methylation as a biomarker, such as its high stability in several biofluids and its dynamism during disease evolution.…”
Section: Methylation Markers From Bench To Bedsidementioning
confidence: 99%
“…Liquid biopsy has drawn major attention in the last few years as a highly useful tool for the management of cancer patients and has already shown its clinical impact on the early detection, minimal residual disease and tracking of treatment resistance [ 17 , 18 ]. The identification of circulating epigenetic biomarkers through DNA methylation studies is of utmost clinical importance in the liquid biopsy field and can be used for the diagnosis, prognosis, and prediction of drug response [ 19 , 20 ]. Notwithstanding that mutation analysis in liquid biopsy is already established through its clinical utility, it cannot always provide consistent results due to tumoral heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt inhibitory factor-1 ( WIF-1 ) has been identified as an important Wnt antagonist which inhibits Wnt/β- catenin signaling by directly binding to Wnt proteins. Methylation of the WIF-1 gene can lead to the loss of WIF-1 expression which has been observed in numerous types of cancer including NSCLC [ 16 , 17 , 18 , 19 , 20 ]. Another important Wnt antagonist with tumor suppressor activity is the APC gene that is involved in cell migration and adhesion, transcriptional activation, and apoptosis; APC promoter methylation has a diagnostic role in NSCLC [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%